Illness narrative: perceptions and lived experiences of kidney recipient clients in Shanghai, China - Chimbatata, Nathan B. W.; Hu, Chao (Science research publishing, 2016)
Terminal kidney disease is a life threatening condition and cause for loss of hope to affected individuals. It affects the individuals physically as well as mentally. The advancement in medical knowledge and technology in transplant surgery has steadily increased the number of kidney recipients. This offers hope for the new lease of life and a wide range of perceptions and experiences with self, society and the new organ. There is minimal research on perceptions and lived experiences of kidney transplant recipients. This study explored the perceptions and lived experiences of individuals with a kidney problem living with a kidney transplant in Shanghai, China. Five indepth interviews were conducted with five clients. The participant’s age ranged from 25 to 45 years. There were three females and two males. Content analysis using NVivo (11.0) software was applied in data analysis. The findings revealed improved quality of life among kidney recipients; however the clients had low knowledge levels on the condition as well as self care practices in the post transplant period. This caused a lot of psychosocial stress in the clients. The post kidney transplant management strategies should include effective education programs to increase awareness on the condition and self care practices so as to reduce factors associated with psychosocial stress in order to improve the quality of life for the clients in the post kidney transplantation period.
Keywords: Kidney Transplant; Psychosocial Stress